COVID-19 in liver transplant candidates: pretransplant and post-transplant outcomes - an ELITA/ELTR multicentre cohort study. Issue 10 (19th July 2021) - Belli, Luca Saverio; Duvoux, Christophe; Cortesi, Paolo Angelo; Facchetti, Rita; Iacob, Speranta; Perricone, Giovanni; Radenne, Sylvie; Conti, Sara; Patrono, Damiano; Berlakovich, Gabriela; Hann, Angus; Pasulo, Luisa; et al.
Abstract : Objective: Explore the impact of COVID-19 on patients on the waiting list for liver transplantation (LT) and on their post-LT course. Design: Data from consecutive adult LT candidates with COVID-19 were collected across Europe in a dedicated registry and were analysed. Results: From 21 February to 20 November 2020, 136 adult cases with laboratory-confirmed SARS-CoV-2 infection from 33 centres in 11 European countries were collected, with 113 having COVID-19. Thirty-seven (37/113, 32.7%) patients died after a median of 18 (10–30) days, with respiratory failure being the major cause (33/37, 89.2%). The 60-day mortality risk did not significantly change between first (35.3%, 95% CI 23.9% to 50.0%) and second (26.0%, 95% CI 16.2% to 40.2%) waves. Multivariable Cox regression analysis showed Laboratory Model for End-stage Liver Disease (Lab-MELD) score of ≥15 (Model for End-stage Liver Disease (MELD) score 15–19, HR 5.46, 95% CI 1.81 to 16.50; MELD score≥20, HR 5.24, 95% CI 1.77 to 15.55) and dyspnoea on presentation (HR 3.89, 95% CI 2.02 to 7.51) being the two negative independent factors for mortality. Twenty-six patients underwent an LT after a median time of 78.5 (IQR 44–102) days, and 25 (96%) were alive after a median follow-up of 118 days (IQR 31–170). Conclusions: Increased mortality in LT candidates with COVID-19 (32.7%), reaching 45% in those with decompensated cirrhosis (DC) and Lab-MELD score of ≥15, was observed, with no significant difference between first and second waves of the pandemic. Respiratory failure was the major cause of death. The dismal prognosis of patients with DC supports the adoption of strict preventative measures and the urgent testing of vaccination efficacy in this population. Prior SARS-CoV-2 symptomatic infection did not affect early post-transplant survival (96%).